Paleobathymetric evolution of the Miocene deposits of the Gombe sector of the Lycian Foreland and Aksu basins in Antalya, Turkey - Kouwenhoven, Tanja; Sis, Fatih Seckin; Koç, Ayten; KAYMAKCI, NURETDİN (TURKISH JOURNAL OF EARTH SCIENCES, 2020)
The evolution of the Lycian Foreland and Aksu basins are associated with the Africa-Eurasia convergence and collision of intervening continental blocks. Both basins developed around the Beydaglari, a Mesozoic carbonate platform, which constitutes the main component and western limb of the Isparta Angle. The Gombe Basin is an integral part of the Lycian Foreland Basin that comprises mainly Eocene to Late Miocene turbidites, onto which the allochthonous Lycian and Antalya nappes thrust over. The Aksu Basin, however, developed in the inner part of the Isparta Angle and is bounded by the Aksu Thrust in the east. During their evolution, these basins experienced significant bathymetric changes, possibly due to vertical motions and variations in the sediment supply. This study provides a detailed analysis of the paleobathymetric evolution of these basins. This conducted paleobathymetric study was based on the determination of the depositional depth by the abundance ratio of planktonic versus benthic foraminifera, which is the function of the water depth. The percentage of planktonic foraminifera relative to the total foraminifer population (%P) increases from shallow to deep water. However, some benthic foraminifera species are directly affected by the oxygen level of the bottom water, rather than by paleobathymetry, i.e. stress markers, and were discarded in the calculation. Additionally, the dissolution of the foraminifera has the potential for miscalculations, since planktonic foraminifera are more prone to dissolution than benthic ones. Nevertheless, the obtained quantitative results were verified and validated qualitatively by specific benthic depth markers that lived at specific depth ranges. Aksu Basin had a shallowing trend, and the sedimentation rate exceeded the subsidence in the middle of the section. Calculated depths for the Gombe Basin indicated depths around 1000 m, which was contrary to the high sedimentation rates indicated by the turbiditic facies of the basin infills.